Studi Empiris Good Corporate Governance (GCG) dan Tata Kelola Keuangan: Ukuran Perusahaan Sebagai Variabel Kontrol: An Empirical Study on Good Corporate Governance (GCG) and Financial Governance: Firm Size as Control Variable - Asrudin Hormati; Nurdin Nurdin; Rinto Syahdan; Irfandi Buamonabot (Society, 2022)
This research explores Good Corporate Governance (GCG) and financial governance by using firm size as a control variable. In particular, this study provides empirical evidence that firm size is a control variable. The sample in this research is companies in the Hotel and Tourism sector listed on the Indonesia Stock Exchange (IDX) period 2013-2018. Data analysis using panel data. The results revealed that of the five proposed hypotheses, only two were accepted. The results show that company size does not fully control the independent variable in this research.